The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1186/1757-1626-2-197
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous superficial peroneal nerve and variant cutaneous innervation of the sural nerve on the dorsum of the foot: a case report

Abstract: BackgroundThe superficial peroneal nerve is a branch of common peroneal nerve. There are reports about the variant course and distribution of this nerve. The sural nerve arises from the tibial nerve in the popliteal fossa. The variations of the above nerves described here are unique and provide significant information to surgeons dissecting lower limb.Case presentationThe present case is about some important anatomic variations observed in left lower limb of approximately 55 - year - old male cadaver. The vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…found 1 case of Spn where it's both branches Mdn and Idn emerge separately and SN supply lateral 1½ digits on dorsum of foot which was similar to our type 4b. [9]…”
Section: Discussionmentioning
confidence: 99%
“…found 1 case of Spn where it's both branches Mdn and Idn emerge separately and SN supply lateral 1½ digits on dorsum of foot which was similar to our type 4b. [9]…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of wounds is an area that has gained a lot of interest from the scientific, medical and industrial communities. For medical device companies, it has been a market that has increased its attractiveness since it involves a large financial dimension around the world, with an annual market for wound care products estimated at $15.3 billion [40]. An increase in the number of advanced and innovative wound dressings is emerging in the market.…”
Section: 32wound Dressings Materialsmentioning
confidence: 99%
“…It has been shown that in the absence of the medial cutaneous branch, the saphenous nerve innervates the medial part of the foot, while in the absence of the lateral cutaneous branch, the sural nerve supplies the lateral part of the dorsum of the foot [4]. A high division of superWcial peroneal nerve into medial and lateral branches, medial branch supplying the medial border of the foot and sural nerve supplying lateral two toes on the dorsum of the foot has been reported by Nagabhooshan et al [9]. Aktan Ikiz et al [2] observed a communication between superWcial and deep peroneal nerve at the Wrst interdigital space in 27.8% of the cases they studied.…”
Section: Discussionmentioning
confidence: 80%